An Evaluation of the Knowledge and Perceptions of Pharmacy Staff and Pre-Registration Students of E-Cigarettes Use: A Systematic Review - Ravina Barrett; Hajar Aldamkhi (SAGE Publishing, 2021)
Introduction: Pharmacy staff are a trusted source of advice on the safe and appropriate use of medicines and devices. Retail pharmacies deliver smoking cessation services and sell e-cigarettes in the UK. This review asks 'what knowledge, experience and ability do staff have to support e-cigarette users to quit smoking'. Methods: A systematic literature search was undertaken drawn on predefined eligibility criteria and a comprehensive search strategy following the PRISMA guideline. Eligible papers reported survey-research published in English from 2015 to 2020. PubMed, Google Scholar, OVID, EMBASE and MEDLINE Databases were searched. No restrictions on study design or language were applied. Two reviewers independently screened for inclusion/exclusion and then extracted the relevant information from the articles for synthesis. Results: Of 12 potentially eligible full-text studies, 1 was a duplicate, 7 were excluded as per eligibility criteria. Four papers were finally included in this literature review. Two studies indicated that pharmacy staff are less confident in giving advice on e-cigarette use. Knowledge on the adverse effects of e-cigarettes compared to traditional smoking cessation aids remain unclear. In one study, 42% of community pharmacists did not believe that e-cigarettes could be used for smoking cessation. Three studies identified need for specific regulations and professional support. The overall certainty of the evidence is 'low' or 'very low', with moderate levels of bias. Conclusion: Pharmacists may be well placed to implement e-cigarette smoking cessation interventions, but most practitioners lacked knowledge and ability to support these customers citing unclear risk of harm. Pharmacists felt secure in recommending traditional cessation tools. Further regulation, guidelines and training is needed. Findings may be less generalizable in countries where e-cigarettes are banned. Their extent of knowledge, experience and ability to support users of e-cigarettes within their community to quit smoking is lacking.